The burden of HIV, syphilis and schistosome infection and associated factors among adults in the fishing communities in northwestern Tanzania. Issue 2 (2nd December 2020) - Kapiga, Saidi; Hansen, Christian H.; Downs, Jennifer A.; Sichalwe, Simon; Hashim, Ramadhan; Mngara, Julius; van Dam, Govert J.; Corstjens, Paul L. A. M.; Kingery, Justin R.; Peck, Robert N.; Grosskurth, Heiner
Abstract: Objectives: To quantify the burden of HIV, syphilis and schistosome infection and associated risk factors among adults living in seven fishing communities of Lake Victoria in northwest Tanzania. Methods: Cross‐sectional study conducted between 2015 and 2016 in the selected communities. In each community, we randomly selected a sample of adults from the general population and from three putative risk groups including the following: (i) fishermen, (ii) fish processors and traders, and (iii) women working in the recreational facilities. Participants were interviewed to obtain information about potential risk factors, and venous blood was collected for detection of HIV, syphilis and schistosome infections. We used logistic regression models to quantify the associations between potential risk factors and HIV, and also between schistosome infection and HIV. Results: We enrolled 1128 people from selected fishing communities. The overall prevalence of HIV, syphilis and schistosome infection was 14.2%, 15.6% and 83.1%, respectively. Female recreational facility workers had the highest prevalence of HIV (30.4%) and syphilis (24%). The odds of being HIV infected were generally higher in all age categories. Transactional sex was commonly reported and especially receiving gifts for sex was found to be strongly associated with HIV (adjusted OR = 2.50; 95% CI: 1.44–4.34, P = 0.008). Confirmed serological syphilis was associated with increased odds of having HIV infection. HIV was not associated with schistosome infection in a combined dataset and when we examined this separately for men and women alone. Conclusions: We observed a high burden of HIV, syphilis and schistosome infections in the fishing communities. Targeted efforts to treat and control infections have the potential to improve health among their residents. Abstract : Objectifs: Quantifier la charge du VIH, de la syphilis et de l'infection à schistosomes et les facteurs de risque associés chez les adultes vivant dans sept communautés de pêcheurs du lac Victoria dans le nord‐ouest de la Tanzanie. Méthodes: Etude transversale menée entre 2015–2016 dans les communautés sélectionnées. Dans chaque communauté, nous avons sélectionné aléatoirement un échantillon d'adultes de la population générale et de trois groupes à risque présumés, notamment: 1) les pêcheurs, 2) les transformateurs et commerçants de poisson et 3) les femmes travaillant dans les établissements de loisirs. Les participants ont été interrogés pour obtenir des informations sur les facteurs de risque potentiels, et du sang veineux a été collecté pour la détection du VIH, de la syphilis et des infections à schistosome. Nous avons utilisé des modèles de régression logistique pour quantifier les associations entre les facteurs de risque potentiels et le VIH, ainsi qu'entre l'infection à schistosome et le VIH. Résultats: Nous avons recruté 1.128 personnes dans une sélection de communautés de pêcheurs. La prévalence globale de l'infection par le VIH, la syphilis et les schistosomes était de 14, 2%, 15, 6% et 83, 1% respectivement. Les travailleuses des établissements de loisirs avaient la prévalence la plus élevée du VIH (30, 4%) et de la syphilis (24%). Les chances d'être infecté par le VIH étaient généralement plus élevées dans toutes les catégories d'âge. Les rapports sexuels transactionnels étaient fréquemment rapportés et surtout le fait de recevoir des cadeaux pour le sexe était fortement associé au VIH (OR ajusté = 2, 50; IC95%: 1, 44–4, 34 ; P = 0, 008). La syphilis sérologique confirmée était associée à une probabilité accrue d'être infecté par le VIH. Le VIH n'était pas associé à une infection à schistosome dans un ensemble de données combinées et lorsque nous avons examiné cela séparément pour les hommes et les femmes. Conclusions: Nous avons observé une charge élevée d'infections par le VIH, la syphilis et les schistosomes dans les communautés de pêcheurs. Des efforts ciblés pour traiter et contrôler les infections ont le potentiel d'améliorer la santé des résidents.